The relevance of Lewis acid sites on the gas phase reaction of levulinic acid into ethyl valerate using CoSBA-xAl bifunctional catalysts. Issue 12 (18th May 2021) - Muñoz-Olasagasti, M.; López Granados, M.; Jiménez-Gómez, C. P.; Cecilia, J. A.; Maireles-Torres, P.; Dumesic, J. A.; Mariscal, R.
Abstract : CoSBA- x Al catalysts show a high yield in the levulinic acid conversion into ethyl valerate. This is due to the presence of weak Lewis acid sites associated with Co 2+ species that have been stabilized by incorporation of Al into the support. Abstract : A series of Co supported on Al-modified SBA-15 catalysts has been studied in the gas phase direct transformation of levulinic acid (LA) into ethyl valerate (EV) using a continuous fixed-bed reactor and ethanol as solvent. It was observed that once the intermediate product gamma-valerolactone (GVL) has been formed, the presence of aluminum is required for the selective transformation to EV. Three Lewis acid sites (LAS) are identified (from highest to lowest acid strength): aluminum ions in tetrahedral and octahedral coordination and Co 2+ sites. The intrinsic activity of these LAS for the key reaction, the GVL ring opening, decreases with the strength of these acid sites, but so does the undesirable formation of coke, also catalyzed by these centers. The best catalyst was that with the highest Al content, CoSBA-2.5Al, that reached an EV yield of up to 70%. This result is associated with the presence of LAS attributed to the presence of Co 2+ surface species that, although having low intrinsic activity in the selective GVL ring-opening reaction, are highly concentrated in this sample and also possess less activity in the undesirable and deactivating formation of coke. These Co 2+ LAS have been stabilized by incorporation of aluminum into the support, modifying the reducibility and dispersion of cobalt species. Additionally, the lower proportion of metallic Co species decreases the hydrogenating capacity of this catalyst. This decrease is a positive result because it prevents GVL hydrogenation to undesired products. This catalyst also showed promising stability in a 140 h on-stream run.